Microalgal transformation of food processing byproducts into functional food ingredients. (January 2022) - Kim, Sunah; Ishizawa, Hidehiro; Inoue, Daisuke; Toyama, Tadashi; Yu, Jaecheul; Mori, Kazuhiro; Ike, Michihiko; Lee, Taeho
Highlights: Global production of categorized food processing byproducts (FPBs) is reviewed. Efficient FPBs pretreatment methods for microalgal cultivation are presented. Food ingredients production from microalgae cultivation using FPBs are discussed. Challenges in microalgal biorefinery of FPBs for circular bioeconomy are addressed. Abstract: Large amounts of food processing byproducts (FPBs) are generated from food manufacturing industries, the second-largest portion of food waste generation. FPBs may require additional cost for post-treatment otherwise cause environmental contamination. Valorization of FPBs into food ingredients by microalgae cultivation can save a high cost for organic carbon sources and nutrients from medium cost. This study reviews FPBs generation categorized by industry and traditional disposal. In contrast with the low-value production, FPBs utilization as the nutrient-abundant medium for microalgae can lead to high-value production. Due to the complex composition in FPBs, various pretreatment methods have been applied to extract the desired compounds and medium preparation. Using the FPB-based medium resulted in cost reduction and a productivity enhancement in previous literature. Although there are still challenges to overcome to achieve economic viability and environmental sustainability, the microalgal transformation of FPBs is attractive for functional food ingredients production.